Zooplankton-population dynamics in the Salado-River basin (Buenos Aires, Argentina) in relation to hydraulic works and resulting wetland function - Bazzuri, María Elisa (2020)
The construction of drainage canals in the upper stretch of the Salado River has caused the input of salty waters into the basin, with unexplored consequences on zooplankton dynamics and reproduction. To determine the consequences of those anthropic interventions, zooplankton samples were taken under four hydrologic conditions (high water, mean flows, low flows, very low flows) in the canals and the river watercourse. Environmental variables were measured in situ (pH, temperature, conductivity, turbidity, flow velocity, water level, dissolved-oxygen concentration) and in the laboratory (chlorophyll a, nutrients). A total of 166 zooplankton taxa was identified, among which rotifers and ciliates were the most diverse and abundant. A redundancy analysis indicated temperature, conductivity, and water discharge to be the main constraints to zooplankton development. Accordingly, abundance peaks were recorded during mean and low flows in the spring and summer, and minimum values during high water (autumn–winter floodings). The dominant species, Brachionus plicatilis s.l., recorded outstanding densities at ca. 34,800 ind L–1—that figure representing a worldwide novelty—during low flows in the canals and at the river downstream site. The wetlands and shallow lakes in the study area acted as sources of inocula for the river, increasing the total abundance of zooplankton, gravid females, nauplii, copepodites, juveniles, and total number of eggs being carried at the second river site downstream from the canals’ discharges. The presence of diverse habitats coupled with the alternation of hydrologic conditions have resulted in the development of a very rich, complex zooplankton community.